PENGARUH AIR PERASAN JERUK NIPIS (Citrus aurantifolia) TERHADAP PERTUMBUHAN BAKTERI Lactobacillus acidophilus - Rachmi Fanani Hakim; Fakhrurazi .; Anisa Editia (Dentistry Faculty, 2018)
Lactobacillus acidophilus is bacteria that has a role play in the caries process. Efforts to controlLactobacillus acidophilus are using antibacterial agents from nature, one of these is lime juice (Citrus aurantifolia). Lime juice has citric acid, flavonoids, saponins, fenols, tannins, alkaloids, and vitamin C thathave different antimicrobial action. The purpose of this study was to determine the effect of lime juice ongrowth of Lactobacillus acidophilus. The research is a laboratory experimental. Antibacterial activity testwas performed using disc diffusion method consisted of 6 treatments and 3 times repetition. MRS-A ispoured into a petri dish and inoculated suspension of Lactobacillus acidophilus, then 6 paper disc that hassoaked into the lime juice concentration of 12.5, 25, 50, 100%, positive control, and negative control placed on an agar medium has cooled. Then the plates were incubated at 37C for 24 hours. Inhibitionzone of microbial growth were measured and recorded after incubation period. These results showed thatlime juice producing growth inhibition zone against Lactobacillus acidophilus on concentration 12,5% is2,2 mm, concentration 25% is 2,3 mm, concentration 50% is 2,4 mm, and concentration 100% is 3,3mm.The statistic calculation result by using One Way ANOVA is p=0,000 with significance p0,05 Theconclusion of this study is the lime juice has weak inhibitory effect on the growth of Lactobacillusacidophilus.Keywords: Lime juice, caries, Lactobacillus acidophilus, disc diffusion method.